Biotechnology of Plastic Waste Degradation, Recycling, and Valorization: Current Advances and Future Perspectives. Issue 19 (9th July 2021) - Qin, Zi‐Hao; Mou, Jin‐Hua; Chao, Christopher Yu Huang; Chopra, Shauhrat Singh; Daoud, Walid; Leu, Shao‐yuan; Ning, Zhi; Tso, Chi Yan; Chan, Chak Keung; Tang, Shixing; Hathi, Zubeen Jyotiwadan; Haque, Md Ariful; et al.
Abstract: Although fossil‐based plastic products have many attractive characteristics, their production has led to severe environmental burdens that require immediate solutions. Despite these plastics being non‐natural chemical compounds, they can be degraded and metabolized by some microorganisms, which suggests the potential application of biotechnologies based on the mechanism of plastic biodegradation. In this context, microbe‐based strategies for the degradation, recycling, and valorization of plastic waste offer a feasible approach for alleviating environmental challenges created by the accumulation of plastic waste. This Minireview highlights recent advances in the biotechnology‐based biodegradation of both traditional polymers and bio‐based plastics, focusing on the mechanisms of biodegradation. From an application perspective, this Minireview also summarizes recent progress in the recycling and valorization of plastic waste, which are feasible solutions for tackling the plastic waste dilemma. Abstract : Plastic biodegradation : Severe plastic wastes pollution requires immediate remediation. As one green alternative, plastic wastes recycling and valorization based on the principle of biodegradation attracts attention from all relevant fields. With the assistance of biotechnology, it could provide feasible solutions for tackling the plastic waste dilemma.